(untitled) (Teacher’s World: Journal of Education and Research, 2023)
Professional preparation is the dynamic and core element that prepares and develops teachers’ professional practices. In Bangladesh, female integration into the high-status profession (like teaching at Dhaka University) has been seen as female empowerment and freedom of choice. Female teachers are a significant and indispensable part of education at the University of Dhaka; currently, thirty-two percent (32%) of its teachers are female. Literature shows that female professionals are not necessarily free from gender prejudice. This research explores by using the development of a qualitative case study how social factors can affect female teachers’ professional preparation and the dynamics of the challenges. Data were collected from one (1) gender specialist and six (6) female faculty members of the University of Dhaka using semi-structured in-depth interviews. The analysis suggested that social factors have substantial effects on female teachers’ professional preparation that limits their professional credibility and competency. The study also identified the challenges that influence social factors. The paper presents a critical observation about the emerging contemporary issues and will contribute to ameliorating cognition about female teachers’ professional development at the University of Dhaka. Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.71-82